P275 An audit of documentation and outcomes in paediatric emergency department presentations of lower respiratory tract infections. (June 2019) - Clark, Allison; Bolger, Turlough
Abstract : Introduction: Lower respiratory infections are a common Paediatric ED presentation. It is important to use resources efficiently in the ED to ensure that those children requiring admission or discharge can be readily identified. We studied the documentation in the medical notes of history, examination and risk factors to assess whether this resulted in appropriate outcomes for patients. Methods: We performed a sequential audit of lower respiratory tract infection presentations to a Paediatric ED using our electronic patient record. We identified 333 presentations over a 6 month period. This includes 316 different patients, as 17 different patients had multiple presentations to the ED for similar symptoms and were subsequently diagnosed with LRTI. Results: Symptoms were evident for an average of 7.48 days (0.5 to 120 days). Patients referred to ED by a doctor in 58% (194/333). Prior treatment, such as inhalers or antibiotic medications was given in 51% of cases (171/333). Risk factors identified for LRTI included history of asthma (55/333), previous admission for a respiratory infection (84/333), preterm birth less than 34 weeks gestation (8/333), previous invasive positive pressure ventilation (10/333), developmental delay/PEG feedings (8/333), and history of immunodeficiency disease (0/333) . Documentation of history of presenting symptoms consistent with LRTI were cough (315/333), fever (235/333), and sputum (98/333). Documentation of the examination findings included respiratory rate only 79% (264/333), oxygen saturation only 49% (162/333), and evidence of work of breathing in 86% (296/333). 251 (75%) chest x-rays were completed while in the ED. Overall, 126/333 patients (38%) were admitted. Looking at subgroups who should predict admission, 74/194 (38%) of GP referrals, those requiring x-ray 112/251 (44%), those who had both fever and sputum present 19/52 (37%), and short duration of symptoms 109/207 (40%) required admission. Discussion: Our documentation of history and examination was generally poor ranging from 49–95%. None of the examined admission risk factors predicted admission suggesting that the clinical formulation and utilisation of resources was haphazard.